Konsumsi Telur Rebus Ayam Vegetarian untuk Meningkatkan Kadar Hb Ibu Postpartum - Renny Sinaga; Safrina Safrina; Vera Renta Siahaan (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Postpartum bleeding is at risk of anemia and maternal death. Postpartum bleeding is related to perineal wounds. Protein is one of the nutrients that has been proven to accelerate the wound healing process, with one popular source being chicken eggs. The purpose of this study was to analyze the differences in the effectiveness of giving boiled vegetarian and domestic chicken eggs to increase hemoglobin levels in postpartum mothers. The design of this study was pretest and posttest with control group. The study sample was 30 1-day postpartum mothers who experienced 1st and 2nd degree perineal tears, who gave birth at the midwife clinic in the Batu Anam Health Center area, selected using purposive sampling technique. A total of 15 postpartum mothers were given vegetarian chicken eggs and 15 postpartum mothers were given domestic chicken eggs. The time of giving chicken eggs was 7 days. Hemoglobin levels were measured in the phases before and after treatment in the group and then compared using the t-test. The results showed that the p value for the difference in hemoglobin levels between before and after treatment in both groups was 0.001 (both treatments could significantly increase hemoglobin levels). The p-value of the comparative test results of the increase between the two groups was 0.001 (the increase in hemoglobin levels was higher in the group given boiled vegetarian chicken eggs). It was concluded that giving boiled eggs successfully increased the hemoglobin levels of postpartum mothers, with the type of vegetarian chicken eggs being significantly better.Keywords: postpartum; hemoglobin; vegetarian chicken eggs ABSTRAK Perdarahan saat postpartum berisiko pada kejadian anemia hingga kematian maternal. Pendarahan postpartum berkaitan dengan luka perineum. Protein merupakan salah satu zat gizi yang terbukti dapat mempercepat proses penyembuhan luka, dengan salah satu sumber yang populer adalah telur ayam. Tujuan penelitian ini adalah menganalisis perbedaan efektivitas pemberian telur rebus ayam vegetarian dan ayam negeri untuk meningkatkan kadar hemoglobin pada ibu postpartum. Rancangan penelitian ini adalah pretest and posttest with control group. Sampel penelitian adalah 30 ibu postpartum 1 hari yang mengalami robekan perineum derajat 1 dan 2, yang bersalin di klinik bidan wilayah kerja Puskesmas Batu Anam, yang dipilih dengan teknik purposive sampling. Sebanyak 15 ibu postpartum diberi telur ayam vegetarian dan 15 ibu postpartum diberi telur ayam negeri. Waktu pemberian telur ayam adalah 7 hari. Pengukuran kadar hemoglobin dilakukan pada fase sebelum dan sesudah perlakuan pada kelompok dan selanjutnya dibandingkan dengan uji t. Hasil penelitian menunjukkan bahwa nilai p untuk perbedaan kadar hemoglobin antara sebelum dan sesudah perlakuan pada kedua kelompok, masing-masing adalah 0,001 (kedua perlakuan dapat meningkatkan kadar hemoglobin secara signifikan). Nilai p hasil uji perbandingan peningkatan antara kedua kelompok adalah 0,001 (peningkatan kadar hemolobin lebih tinggi pada kelompok yang diberi telur rebus ayam vegetarian). Disimpulkan bahwa pemberian telur rebus berhasil meningkatkan kadar hemoglobin ibu postpartum, dengan jenis telur ayam vegetarian secara signifikan lebih baik. Kata kunci: postpartum; hemoglobin; telur ayam vegetarian